Trivial and Important Criteria for Social Categorization in the Minimal Group Paradigm - Moghaddam, Fathali M.; Stringer, Peter (The Journal of social psychology, 1986)
The study examined how the importance of a criterion for social categorization can vary with the social context. The main hypothesis was that there would be no difference between the influence of two criteria of differing real-world importance when each is used independently as the only criterion for social categorization in the same minimal group setting. The subsidiary hypothesis was that social categorization on both a trivial and an important basis would lead to positive in-group bias. The subjects were 66 schoolboys. Social categorization was on the basis of either a minimal criterion or subjects' school house-system. Both the main and the subsidiary hypotheses were confirmed.